RITUAL POPANGA PADA ETNIK MUNA - hesni hesni; Wa Kuasa (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2018)
This research was conducted in Wakuni Village, Sawerigadi District, West Muna Regency with the aim of knowing the process of implementation, symbolic meaning, and the values contained in the Popanga ritual of the Muna ethnic group. The method used in this study isdescriptive qualitative. Data collection is done by observation (observation), in-depth interviews,and documentation. The technique of determining informants in this study was conducted bypurposive sampling, while the informants in this study were 6 people consisting of religiousleaders, traditional leaders, community leaders and other informants who knew the custom. Thedata analysis technique in this study consists of three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study show that the process ofperforming the popanga ritual has several stages, namely (1) the stage of preparation for theritual popanga (2) the stage of implementation (3) the stage of the kasolo (looking at thesituation). The symbolic meaning in the popanga ritual is divided into two types, namely (1) themeaning of tools and offerings (2) the meaning of speech. The valuescontained in the popanga ritual are religious values, cultural values, and social values.